Prolonged severe acute respiratory syndrome coronavirus 2 persistence, attenuated immunologic response, and viral evolution in a solid organ transplant patient. Issue 2 (20th September 2021) - Purpura, Lawrence J.; Chang, Michelle; Annavajhala, Medini K.; Mohri, Hiroshi; Liu, Lihong; Shah, Jayesh; Cantos, Anyelina; Medrano, Nicola; Laracy, Justin; Scully, Brian; Miko, Benjamin A.; Habal, Marlena; et al.
Abstract : Unlike immunocompetent hosts, the duration of viral persistence after infection with severe acute respiratory syndrome coronavirus 2 can be prolonged in immunosuppressed patients. Here, we present a case of viral persistence for over 19 weeks in a patient with a history of solid organ transplant and explore the clinical, virologic, and immunologic course. Our patient still demonstrated viral persistence at 138 days with low polymerase chain reaction cycle threshold values and evidence of continuing viral sequence evolution indicative of ongoing virus replication. These findings have important implications for infection prevention and control recommendations in immunosuppressed patients. Immune response, including neutralizing antibody titers, T cell activity, and cytokine levels, peaked around days 44–72 after diagnosis. Anti‐S trimer antibodies were low at all time points, and T cell response was attenuated by day 119. As immune response waned and viral load increased, increased genetic diversity emerged, suggesting a mechanism for the development of viral variants. Abstract : SARS‐CoV‐2 persistence for over 19 weeks with evidence of continuing viral evolution are reported in a heart transplant recipient.